2016
DOI: 10.1016/j.actbio.2016.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Combination scaffolds of salmon fibrin, hyaluronic acid, and laminin for human neural stem cell and vascular tissue engineering

Abstract: Human neural stem/progenitor cells (hNSPCs) are good candidates for treating central nervous system (CNS) trauma since they secrete beneficial trophic factors and differentiate into mature CNS cells; however, many cells die after transplantation. This cell death can be ameliorated by inclusion of a biomaterial scaffold, making identification of optimal scaffolds for hNSPCs a critical research focus. We investigated the properties of fibrin-based scaffolds and their effects on hNSPCs and found that fibrin gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 110 publications
(168 reference statements)
2
89
0
Order By: Relevance
“…A similar result was obtained when fibrin and HA were mixed at a ratio of 2.5:1.5 (final concentrations of fibrin and HA were 2.5 and 1.5 mg/ml, respectively), and most astrocytes had protrusions. This result agreed well with previous reports (Arulmoli et al, ; Levy et al, ; Placone et al, ). Vascular morphology, such as vessel width and lumen structure, was not significantly affected up to the addition of 1.5 mg/ml HA, whereas the effect of HA on astrocyte morphology was saturated at this ratio.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…A similar result was obtained when fibrin and HA were mixed at a ratio of 2.5:1.5 (final concentrations of fibrin and HA were 2.5 and 1.5 mg/ml, respectively), and most astrocytes had protrusions. This result agreed well with previous reports (Arulmoli et al, ; Levy et al, ; Placone et al, ). Vascular morphology, such as vessel width and lumen structure, was not significantly affected up to the addition of 1.5 mg/ml HA, whereas the effect of HA on astrocyte morphology was saturated at this ratio.…”
Section: Resultssupporting
confidence: 94%
“…Brain tissue is composed of complex ECM components, including HA, proteoglycans, and tenascins (Zimmermann & Dours‐Zimmermann, ). Among cells in the human BBB microenvironment, astrocyte phenotype and morphology are known to be influenced greatly by the local microenvironment (Arulmoli et al, ; Levy et al, ). This was clearly demonstrated by Placone et al (), who manipulated the type and ratio of the ECM including HA and then analyzed astrocyte morphology and active states under each ECM condition.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Bardsley et al 43 showed in his study high initial in vitro degradation of fibrin gel between 0 and 5 days. It was shown that the degradation rate can be slowed down by combining with hyaluronic acid and laminin 42 or polyethylenglycol. 45 While fibrin-only gel totally degrades after 14 days of cultivation, PEGylated fibrin stayed intact.…”
mentioning
confidence: 99%
“…Previous study indicated that combination scaffolds consisting of fibrin with HA and laminin provide biomaterial properties to enable polymerization with cells. This mimics the native tissue of the brain and supports differentiation of human neural stem/progenitor cell (hNSPC) function [27]. Currently, HA-based biomaterials are used to regulate the cell differentiation and studied for tissue engineering purposes in combination with growth factors or ECM components for tissue repair [2833].…”
Section: Introductionmentioning
confidence: 99%